Enhancing the professional development of adapted physical education teachers in Russia and Serbia: challenges and best practice - Tregubova T.M. ,; Papić-Blagojević Nataša ,; Ozerova O.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to conduct a comparative analysis of training and professional development programs for teachers of adapted physical education in Russia and Serbia to identify similarities and differences between the two systems, which operate in accordance with their national regulations. Methods and structure of the study. This paper examines the current legal framework governing teachers' professional development, along with the procedures and regulations that shape this process within the educational systems of Russia and Serbia. By analyzing theoretical frameworks and existing training programs, it provides insights into the extent to which teacher development supports the successful implementation of educational reforms, according to modern challenges and trends. Results and conclusions. Research has shown that the regulations introduced in Russia and the Republic of Serbia over the past decade have significantly increased awareness of the importance of professional development for teachers in the field of adapted physical education. The available programs have the potential to encourage greater teacher participation in this specialized area of physical education. There are a lot of similarities in the systems of professional development of adaptive physical education teachers in Russia and Serbia, but there are also significant differences. Among even models of professional development and advanced training that are similar in form, there are their own specifics and some differences in relation to: the mandatory nature of professional development, time of retraining and advanced training (working, non-working), the number of mandatory hours (from 15 to 166 hours), frequency (from once every 5 years to annual training), the degree of centralization of advanced training management - centralized and decentralized, etc.